Multidisciplinary Treatment for Childhood Obesity: A Two-Year Experience in the Province of Naples, Italy - Francesca Gallè; Giuliana Valerio; Ornella Daniele; Valentina Di Mauro; Simone Forte; Espedita Muscariello; Roberta Ricchiuti; Serena Sensi; Mario Balia; Giorgio Liguori; Pierluigi Pecoraro (MDPI AG, 2022)
Childhood obesity must be faced through an integrated multi-level preventive approach. This study was aimed at assessing the adherence and the outcomes of an outpatient service for childhood obesity treatment activated in the province of Naples, Italy, throughout a 2-year follow-up period. At first visit (T0), weight, height, waist circumference, and body composition of children were assessed, together with sociodemographic features and physical activity levels of children and parents. Anthropometric and body composition parameters of children were measured at 6 ± 3 months (T1) and 12 ± 3 months (T2). A total of 451 non-related children who accessed the service were analyzed: 220 (48.7%) of them returned at least once (attrition rate 51.3%). Returner outpatients showed higher age (p = 0.046) and father's educational level (p = 0.041) than non-returner ones. Adherence to the treatment was found to be related to father's (Rho = 0.140, p = 0.005) and mother's (Rho = 0.109, p = 0.026) educational level. All the outcomes improved between T0 and T1 (p < 0.001), while only body mass index (BMI) decreased significantly at T2. Changes in BMI-SDS were associated with baseline value (OR 0.158, 95%CI 0.017-0.298, p = 0.029). The multidisciplinary approach seems to be promising to treat childhood obesity in this geographic context. Lower parents' educational level should be considered as an attrition determinant.